Reduced antibody responses against Plasmodium falciparum vaccine candidate antigens in the presence of Trichuris trichiura - Esen, Meral; Mordmüller, Benjamin; de Salazar, Pablo Martinez; Adegnika, Ayola Akim; Agnandji, Selidji Todagbe; Schaumburg, Frieder; Hounkpatin, Aurore Bouyoukou; Brückner, Sina; Theisen, Michael; Bélard, Sabine; Ngoa, Ulysse Ateba; Issifou, Saadou; et al. (Vaccine, 2012)
► The malaria vaccine candidate GMZ2 induces antibody responses. ► Infection with Trichuris trichiura is associated with a decreased response against vaccine antigens. ► Other intestinal helminths had no measurable effect on immune responses against the vaccine. ► Future vaccine trials in helminth-affected populations should take into account infection status. Helminth infections are highly prevalent in the tropics and may have an effect on immune responses to vaccines due to their immunomodulatory effect. The prevalence of helminth infections in young children, the target group for malaria and most other vaccines, is high. Therefore we assessed the influence of helminth infection on vaccine-induced immune responses in a phase I clinical trial of the malaria vaccine candidate GMZ2. Twenty Gabonese preschool-age children were vaccinated with GMZ2, a blood stage malaria vaccine candidate. Humoral immune response against the vaccine antigens and parasitological status were assessed. Vaccine-specific antibody concentrations and memory B-cell numbers were compared in worm infected and non-infected participants. Antibody response to GMZ2 was 3.4-fold (95% confidence interval: 1.6, 7.4) higher in Trichuris trichiura negative subjects compared to positive participants, whereas immunoglobulin subclass distribution was similar. Memory B-cell response was moderately increased in T. trichiura negative individuals, although the difference was not significant. Future malaria vaccine development programs need to account for worm-mediated hyporesponsiveness of immune reactions.